Interactive effects of temperature, ultraviolet radiation and food quality on zooplankton alkaline phosphatase activity - Wolinski, Laura Isabel (2016)
Ultraviolet Radiation (UVR) is a stressor for aquatic organisms affecting enzyme activities in planktonic populations because of the increase in reactive oxygen species. In addition, UVR exposure combined with other environmental factors (i.e. temperature and food quality) could have even higher detrimental effects. In this work, we aimed to determine the effect of UVR on somatic Alkaline Phosphatase Activity (APA) and Glutathione S-Transferase (GST) activity on the cladoceran Daphnia commutata under two different temperatures (10 °C and 20 °C) and under three food qualities (carbon:phosphorus ratios: 1150, 850 and 550). APA is a biomarker that is considered as a P deficiency indicator in zooplankton. Since recovery from UVR damage under dark conditions is an ATP depending reaction we also measured APA during recovery phases. We carried out a laboratory experiment combining different temperatures and food qualities with exposition to UVR followed by luminic and dark phases for recovery. In addition, we exposed organisms to H2O2, to establish if the response on APA to UVR was a consequence of the reactive oxygen species produced these short wavelengths. Our results showed that somatic APA was negatively affected by UVR exposure and this effect was enhanced under high temperature and low food quality. Consistently, GST activity was higher when exposed to UVR under both temperatures. The H2O2 experiments showed the same trend as UVR exposure, indicating that APA is affected mainly by oxidative stress than by direct effect of UVR on the enzyme. Finally, APA was affected in the dark phase of recovery confirming the P demands. These results enlighten the importance of food quality in the interacting effect of UVR and temperature, showing that C:P food ratio could determine the success or failure of zooplanktonic populations in a context of global change.